GARM: Genome Assembly, Reconciliation and Merging Pipeline - Mayela Soto-Jimenez, Luz; Estrada, Karel; Sanchez-Flores, Alejandro (Current Topics in Medicinal Chemistry, 2014)
Over the past decades DNA sequencing technologies have been improving in aspects like quality, read length, runtimes and yields, all at a lower cost. Despite these improvements, genome assembly remains a challenge in genome sequencing projects, especially when different sequencing platforms are used. At the present, there is no program that can handle and assemble different sequencing technologies better than specialized software for each of them. Also, very few protocols are available for merging results from different algorithms, technologies or both. We present GARM, (Genome Assembler, Reconciliation and Merging) a pipeline to merge assemblies from different algorithms or sequencing technologies.
Keywords: next-generation sequencing